Fast detection of deletion breakpoints using quantitative PCR - Gulshara Abildinova; Zhanara Abdrakhmanova; Helena Tuchinsky; Elimelech Nesher; Albert Pinhasov; Leon Raskin (Genetics and Molecular Biology, 2016)
Abstract The routine detection of large and medium copy number variants (CNVs) is well established. Hemizygotic deletions or duplications in the large Duchenne muscular dystrophy DMD gene responsible for Duchenne and Becker muscular dystrophies are routinely identified using multiple ligation probe amplification and array-based comparative genomic hybridization. These methods only map deleted or duplicated exons, without providing the exact location of breakpoints. Commonly used methods for the detection of CNV breakpoints include long-range PCR and primer walking, their success being limited by the deletion size, GC content and presence of DNA repeats. Here, we present a strategy for detecting the breakpoints of medium and large CNVs regardless of their size. The hemizygous deletion of exons 45-50 in the DMD gene and the large autosomal heterozygous PARK2 deletion were used to demonstrate the workflow that relies on real-time quantitative PCR to narrow down the deletion region and Sanger sequencing for breakpoint confirmation. The strategy is fast, reliable and cost-efficient, making it amenable to widespread use in genetic laboratories.